Emerging from the war: Gold standard mentality, current accounts and the international business cycle 1885-1939 - Mathias Hoffmann; Ulrich Woitek (University of Zurich, Department of Economics, 2011)
We study international business cycles and capital flows in the UK, the United States and the Emerging Periphery in the period 1885-1939. Based on the same set of parameters, our model explains current account dynamics under both the Classical Gold Standard and during the Interwar period. We interpret this as evidence for Gold Standard mentality: the expectation formation mechanism with respect to major macroeconomic variables driving the current account - output, exchange rates and interest rates - has remained fundamentally stable between the two periods. Nonetheless, the macroeconomic environment changed: Volatility increased generally, but less so for international capital flows than for GDP. This pattern is consistent with shocks in the Interwar period becoming more persistent and more global.
Keywords: F32; F36; F40; F41; N1; 330; Current Accounts; Capital Flows; Business Cycles; Great Depression; Gold Standard; Emerging Markets; Present-Value models; Leistungsbilanz; Kapitalmobilität; Konjunkturzusammenhang; Großbritannien; USA; Welt